Transformation of arsenic species from seafood consumption during in vitro digestion - Liu, Bei; Sui, Jianxin; Feng, Ruixue; Lin, Hong; Han, Xiangning; Sun, Xun; Cao, Limin (Frontiers in Nutrition, 2023)
The arsenic (As) species analysis is important for risk evaluation of seafood. Till now there is limited information on the change of As species during digestions. Here the As species in different seafood before and after in vitro digestion were investigated. While inorganic As was not detected in digested fish samples, As(V) contents in digested crabs and scallops were 17.12±1.76 and 138.69±7.53, respectively, which was approximately 2-3 times of the pre-digestion samples. In further experiments, arsenocholine, dimethylarsinate, arsenobetaine and monomethylarsonate were all convertible to As(Ⅴ) during in vitro digestions with different rate. The transformation demonstrates a complex process and could be affected by many factors such as pH, time and digestion juice composition, where the pH seemed to be particularly important. Free radicals were found responsible for the oxidation in the transformation reactions. Unlike arsenobetaine, arsenocholine seemed able to directly transform to monomethylarsonate without the intermediate dimethylarsinate. This study reveals and validates the potential of other species (oAs or/and unknown species) to convert to iAs, identifies the main factors affecting this process, and proposes a reaction pathway. There is an important implication for promoting more accurate risk assessment of arsenic in foodstuffs.